Integrated Effect of FYM and Potassium Humate on Mulberry Leaves and Bioassay of Silkworm in Acid Soils of Kalimpong Hills - Ram, R. L.; Chatterjee, S.; Maji, C.; Sharma, P. K.; Singh, Y. V. (International Journal of Bio-resource and Stress Management, 2017)
A field experiment was conducted during 2014–16 at Regional Sericultural Research Station farm in Kalimpong hills, West Bengal with six treatments and four replications to study the integrated effect of FYM and potassium humate (KH) on growth attribute characters, leaf yield and quality of existing BC259 (Morus alba L.) mulberry variety. This experiment was also extended to check its adverse effect on bioassay of SK6×SK7 (Bombyx mori L.) silkworm. Based on data analyzed, it was found that, the highest annual leaf yield 14.97 mt ha-1 was recorded after the application of FYM @ 10 mt+KH @ 25 kg+NPK @ 150:50:50 kg ha-1, however, only 12.00 mt ha-1 leaf yield was recorded in control after the application of FYM @ 10 mt ha-1+NPK @ 150:50:50 kg ha-1. The total leaf yield gain in above treatment was 24.74% higher than control.The nutritional quality like moisture content 76.78%, total chlorophyll 1.77 mg g-1, total soluble protein 24.78 mg g-1, total soluble sugar 36.23 mg g-1, total carbon 43.77%, total ash 12.46%, total N 3.58%, total P 0.35% and crude protein 22.40% were also recorded as higher side over control. Bioassay of silkworm reveals that, the mulberry leaves of above treatment have significant result on single cocoon weight, cocoon yield 100 dfls-1 and shell% respectively. The higher cost benefit ratio was also recorded as 1:1.92% with net profit ` 1.69 Lakhs ha-1 year-1 after the application of above treatment than control.